Effect of Sewage Treatment Plant Effluent on Water Quality of Zhangze Reservoir Based on EFDC Model - Yang, Long; Wei, Jia; Qi, Jun; Zhang, Min (Frontiers in Environmental Science, 2022)
Understanding how external water affects the water quality of target water bodies is an important prerequisite for predicting water quality changes and formulating pollutant reduction plans. Using the EFDC modeling system platform, this study constructed the hydrodynamic and pollutant dispersion and diffusion models of Zhangze Reservoir, and by using the hydrology and water quality data from 2013 to 2018, this study examines the different water quality responses of Zhangze Reservoir under different inflow water control scenarios. The results show that the simulated value of the hydrological station is basically consistent with the measured value of the hydrological station. Under the current Class III water quality requirements for Zhangze Reservoir, direct inflow of effluent from the wastewater treatment plant of the main urban area into the reservoir will have a significant impact on the water quality. When the effluent is purified through constructed wetlands, it significantly improves the water quality of the reservoir, but the concentration of TN and TP still cannot reach the Class III standard in the short term,. When all rivers entering the reservoir meet the standard and the effluent from the wastewater treatment plant in the main urban area does not enter the reservoir, the content of COD, ammonia nitrogen and TP in water will reach the Class III standard, but reducing the TN content to meet the standard requirement will be difficult within 3 years.